Application of the Response Elaboration Training (RET) Method on Narrative Ability in Aphasia Patients in Surakarta City - Feby Ahadiyatul Aminah; Muryanti Muryanti; Nadya Susanti (Indonesian Journal of Global Health Research, 2025)
Aphasia is the loss of language function due to brain damage in an area associated with language comprehension and production. Patients with aphasia need a method that can be used to aid language recovery, one of which uses the method of response elaboration training (RET) by providing a stimulus for narrative ability through speech prompting. The purpose of this study was to determine the effectiveness of the application of the Response Elaboration Training (RET) method on storytelling ability in aphasia patients in Surakarta City. This study experimental with a one-group pretest-posttest design and five intervention using the response elaboration training (RET) method. The total sampling technique with the of respondents in this study amounted to 15 respondents with aphasia. The Wilcoxon test was used for data analysis. Results of the Wilcoxon test obtained a p-value (Sig.) of 0.001 (p-value <0.05), so it can be concluded that there is an efficacy of the aphasia training. There is an effectiveness of the application of the response elaboration training (RET) method on the narrative ability of aphasia patients in Surakarta City.